Upaya Meningkatkan Minat Belajar Mata Pelajaran Pendidikan Agama Islam Melalui Model Pembelajaran Moving Class Di Kelas VIII SMP Al Hikmah Tanjung Pura - Fiqri Yulhakim; Satria Wiguna; Usmaidar Usmaidar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research uses a moving class learning model. By using the Moving Class system, it is hoped that it will increase student activity and interest in learning. The Moving Class learning model has the characteristics of private classes according to certain subjects. Based on the implementation of Moving Class, not many schools have implemented it, but schools have also implemented this system. For this reason, the researcher will explain about Moving Class so that readers have an idea about Moving Class and how to apply it. This research uses a classroom action research approach (action research) where this research has two cycles, data collection methods by means of observation, documentation, and test techniques. The results of the research show that the learning outcomes of students in the pre-cycle were 27.5%, Cycle I with a completion percentage of 72.5% and cycle II with a completion percentage of 92.5%. From pre-cycle I to cycle II, everyone experienced significant improvement. When implementing the Moving Class system, that is, the class must have lots of complete facilities and adequate media, class cleanliness must be maintained, and be on time when changing classes.